F199E substitution reduced toxicity of Clostridium perfringens epsilon toxin by depriving the receptor binding capability - Jingjing Kang; Jie Gao; Wenwu Yao; Lin Kang; Shan Gao; Hao Yang; Bin Ji; Ping Li; Jing Liu; Jiahao Yao; Wenwen Xin; Baohua Zhao; et al. (Taylor & Francis Group, 2017)
Epsilon toxin (ETX), a potent toxin, is produced by types B and D strains of Clostridium perfringens, which could cause severe diseases in humans and domestic animals. Mutant rETXF199E was previously demonstrated to be a good vaccine candidate. However, the mechanism concerned remains unknown. To clarify how F199E substitution reduced ETX toxicity, we performed a series of experiments. The results showed that the cell-binding and pore-forming ability of rETXF199E was almost abolished. We speculated that F199E substitution reduced toxicity by depriving the receptor binding capability of ETX, which contributed to the hypothesis that domain I of ETX is responsible for cell binding. In addition, our data suggested that ETX could cause Ca2+ release from intracellular Ca2+ stores, which may underlie an alternate pathway leading to cell death. Furthermore, ETX induced crenation of the MDCK cells was observed, with sags and crests first appearing on the surface of condensed MDCK cells, according to scanning electron microscopy. The data also demonstrated the safety and potentiality of rETXF199E as a vaccine candidate for humans. In summary, findings of this work potentially contribute to a better understanding of the pathogenic mechanism of ETX and the development of vaccine against diseases caused by ETX, using mutant proteins.